PENGARUH PELATIHAN PASAR MODAL, RETURN, PERSEPSI RISIKO, GENDER, DAN KEMAJUAN TEKNOLOGI PADA MINAT INVESTASI MAHASISWA - Tandio, Timothius; Widanaputra, A.A G.P (E-Jurnal Akuntansi, 2016)
This research aims to test an effect of capital market training, return, perception of risk, gender and technological advances to interest of investment. The researcher wish to see factors that affect investment interest of university student which notabene have no experience at stock investment in capital market . Data in this research obtained directly using a questionnaire from 95 respondents. The sampling method was Purposive sampling. The nominal form of primary data then converted to interval quantitative data using method of successive interval. Based on analytic regression, capital market training and return significantly affect interest of investment. Test also found “interesting” matter, perception of risk, gender and technological advances variable are not affecting interest of investment significanly . Differ from previous researches, university student’s perception about risk does not affect their interest to investing in capital market.
Keywords: capital market, capital market training, education, gender, investment, investment interest, return, risk, stock, technology